Visible Light Communication System Design and Link Budget Analysis - Hussain, Babar; Xianbo Li; Fengyu Che; Patrick Yue, C.; Liang Wu (Journal of lightwave technology, 2015)
This paper presents, for the first time, a systematic approach to visible light communication (VLC) transceiver design based on an analytical optical wireless link budget study. To obtain the signal-to-noise ratio at the receiver, the received signal power is predicted by modeling the transmitted optical power and the channel path loss, while the input-referred noise is estimated by characterizing the noise contribution from each of the receiver building blocks. Based on the targeted bit error rate (BER) and communication distance, a VLC transceiver using discrete components and a fully integrated CMOS VLC transmitter compliant with the IEEE 802.15.7 Standard have been designed and tested. Experimental results show that the measured BER agrees well with the proposed model for both the systems, validating our design approach and the link budget analysis.